2015
DOI: 10.4236/jbm.2015.310012
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Factors Associated with Anemia Pregnancy in a Group of Moroccan Pregnant Women

Abstract: Background: Pregnancy is typically accompanied by an increase of micronutrient requirements in general and especially iron. This increased need may be an additional risk factor for developing anemia. Purpose of the study: The aim of this study is to provide data on the prevalence of anemia of pregnancy in the maternity ward of the regional hospital in the city of Temara, and examine risk factors that may expose women to anemia during pregnancy. Materiel and Methods: A prospective cross-sectional study of a yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 8 publications
3
10
1
1
Order By: Relevance
“…Studies conducted elsewhere have reported the association between drinking tea or coffee at meal times and anemia in pregnancy ( 37 , 38 ). The prevalence of anemia in this study is not in line with the studies conducted in Ethiopia, Ghana, and Morocco, which showed lower prevalences of anemia (32.8%, 50.8%, and 57.6%, respectively) ( 39 41 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Studies conducted elsewhere have reported the association between drinking tea or coffee at meal times and anemia in pregnancy ( 37 , 38 ). The prevalence of anemia in this study is not in line with the studies conducted in Ethiopia, Ghana, and Morocco, which showed lower prevalences of anemia (32.8%, 50.8%, and 57.6%, respectively) ( 39 41 ).…”
Section: Discussioncontrasting
confidence: 99%
“…According World Health Organization 9 , our group is qualified as a population with severe anemia (more than 40%). Our results are in agreement with the results of other studies, 43.4% in Algeria 12 45.4% in Egypt 4, and 43.2% in Cameroon 13 , but they are higher than other regions in Morocco: 16.8% in Temara city 14 and 14.4% in Casablanca 15 . This difference is explained by disparities in living conditions between regions in Morocco, and the repercussions of the precarious living conditions on the population health, especially in rural area 16 .…”
Section: Discussionsupporting
confidence: 93%
“…However, pregnancy anemia, even moderate, when it is related to iron deficient, is a risk factor for preterm birth, and a growth retardation of newborn 12,21 . Several studies have confirmed the association of anemia with demographic, socioeconomic and cultural factors 22,23,14,12,18,24 . The present study has shown that the rural origin of the woman, her young age, illiteracy and low educational attainment, inactivity, low socioeconomic status and primiparity are the determinants that pro- Table II: Association between bio-demographic, socio-economic and cultural characteristics and anemia among pregnant women mote the development of anemia in pregnant women.…”
Section: Discussionmentioning
confidence: 94%
“…The prevalence of anaemia in this study is higher than a study conducted in Ethiopia, Indian and Morocco, which showed that prevalence of anaemia were 27.6%, 41.5% and 57.6% respectively. [17][18][19] The difference observed in these studies could be due to geographical factors and difference in nutrition practices among pregnant women. The prevalence of anaemia in this study is also higher than the national anaemia prevalence of 48% and 60% in Zanzibar.…”
Section: Discussionmentioning
confidence: 99%